Higher education research methodology : a step-by-step guide to the research process - Daniel, Ben Kei, 1971-; Harland, Tony, 1955-; Wald, Navé (Oxon: Routledge, 2018)
"With new chapters and updated content throughout, this second edition of Higher Education Research Methodology is an essential guide to systematic inquiry into higher education. Providing practical and theoretical guidance for students, topics covered include ontology and epistemology, as well as research design approaches and methods of data collection. New to this edition are two brand new chapters on conceptual and theoretical frameworks, and research justification, as well as a comprehensive revision of the chapter on engaging with academic literature. Throughout the book there is a keen focus on quality in both the analysis and evaluation of research and new models are proposed to help the new researcher. The authors provide advice as well as constructive critique of research methods and, in turn, offer a new contribution to the theories of research methodology. Looking beyond the immediate higher education environment, the book concludes by examining the challenges of getting work published and providing guidance on how to do this successfully. Thoroughly revised, this new edition of Higher Education Research Methodology will be of interest to postgraduate students, academic developers and experienced academics from a wide variety of disciplines"--
Includes bibliographical references and index.
Keywords: Education, Higher -- Research -- Methodology